Gating Kinetics of Single Large-Conductance Ca(2+)-Activated K(+) Channels in High Ca(2+) Suggest a Two-Tiered Allosteric Gating Mechanism(✪) - Rothberg, Brad S. (The Rockefeller University Press, 1999)

(untitled)
The Ca(2+)-dependent gating mechanism of large-conductance calcium-activated K(+) (BK) channels from cultured rat skeletal muscle was examined from low (4 μM) to high (1,024 μM) intracellular concentrations of calcium (Ca(2+) (i)) using single-channel recording. Open probability (P (o)) increased with increasing Ca(2+) (i) (K (0.5) 11.2 ± 0.3 μM at +30 mV, Hill coefficient of 3.5 ± 0.3), reaching a maximum of ∼0.97 for Ca(2+) (i) ∼ 100 μM. Increasing Ca(2+) (i) further to 1,024 μM had little additional effect on either P (o) or the single-channel kinetics. The channels gated among at least three to four open and four to five closed states at high levels of Ca(2+) (i) (>100 μM), compared with three to four open and five to seven closed states at lower Ca(2+) (i). The ability of kinetic schemes to account for the single-channel kinetics was examined with simultaneous maximum likelihood fitting of two-dimensional (2-D) dwell-time distributions obtained from low to high Ca(2+) (i). Kinetic schemes drawn from the 10-state Monod-Wyman-Changeux model could not describe the dwell-time distributions from low to high Ca(2+) (i). Kinetic schemes drawn from Eigen's general model for a ligand-activated tetrameric protein could approximate the dwell-time distributions but not the dependency (correlations) between adjacent intervals at high Ca(2+) (i). However, models drawn from a general 50 state two-tiered scheme, in which there were 25 closed states on the upper tier and 25 open states on the lower tier, could approximate both the dwell-time distributions and the dependency from low to high Ca(2+) (i). In the two-tiered model, the BK channel can open directly from each closed state, and a minimum of five open and five closed states are available for gating at any given Ca(2+) (i). A model that assumed that the apparent Ca(2+)-binding steps can reach a maximum rate at high Ca(2+) (i) could also approximate the gating from low to high Ca(2+) (i). The considered models can serve as working hypotheses for the gating of BK channels.